Creative artists or cultural practitioners? Holistic practice in Australia's cultural industries - Bennett, Dawn (University of Queensland, 2007)
Despite, or perhaps because of, changes in the perception of culture, definitions for the cultural industries vary between different locations, organisations, and the objectives of the documents within which they are contained. The lack of an agreed definition for the cultural industries - within Australia and internationally - impacts data collections which inform funding, education, training, policy and advocacy. It also inhibits effective research into the needs and circumstances of artists. As decision-makers struggle for understanding of the requirements for sustainable practice within parameters that are unclear, many artists are left floundering with little long-term, practical support. This paper examines the cultural environment in which artists conduct their practice; a practice which most often involves a diverse range of activities and skills far beyond the stereotype of a creator or performer. The text draws from a study which comprised an extensive review of statistical data and literature, a study of over three hundred musicians, and interviews with economists, social researchers, practitioners, and arts organisations. The findings led to a practitioner-focussed cultural industries framework, which illustrates a breadth of cultural activities and their statistical labels; draws attention to the numerous activities currently reported as 'not elsewhere classified'; and highlights the diversity of roles available to practitioners.